Analysis Of The Design Of The Inpatient Medical Record Completeness Audit Application At Prof. Dr. Margono Soekarjo Purwokerto Regional Hospital - Meganingtyas, Elisabeth Yuga Nova; Wulandari, Sri (International Journal of Computer and Information System (IJCIS), 2025)
The completeness of inpatient medical records plays a vital role in ensuring the quality of healthcare services and compliance with hospital accreditation standards. This study aims to design an inpatient medical record audit application that addresses existing inefficiencies in manual audit processes at RSUD Prof. Dr. Margono Soekarjo Purwokerto. The research was conducted using the System Development Life Cycle (SDLC) with a waterfall model approach, consisting of needs analysis, system design, coding, and testing. Data collection involved observation and interviews with inpatient coding staff, which revealed several issues in the current Google Spreadsheet-based audit system, including inflexible checklists, high risk of data loss, poor synchronization, and duplicate entries. The proposed web-based application offers functional features such as multi-user login, patient data upload, dynamic checklists, open and close audit forms, and graphical audit reports. Non-functional requirements emphasize security, accessibility, simplicity, and responsiveness. User requirements focus on ease of navigation, printable reports, and support for daily work routines. The system was implemented using JavaScript and tested through black-box testing, which confirmed all functionalities performed as expected. User satisfaction was evaluated through a questionnaire distributed in the medical records department with 13 respondents, 1 department head and 12 coders, the results showed an overall satisfaction level of 92.59%. This application improves audit efficiency, reduces input errors, and supports hospital efforts to meet accreditation indicators. The findings suggest that a well-designed information system can significantly enhance the management and monitoring of medical record completeness.